2016
DOI: 10.1364/boe.7.001311
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte-derived nano-probes functionalized with antibodies for targeted near infrared fluorescence imaging of cancer cells

Abstract: Constructs derived from mammalian cells are emerging as a new generation of nano-scale platforms for clinical imaging applications. Herein, we report successful engineering of hybrid nano-structures composed of erythrocyte-derived membranes doped with FDA-approved near infrared (NIR) chromophore, indocyanine green (ICG), and surfacefunctionalized with antibodies to achieve molecular targeting. We demonstrate that these constructs can be used for targeted imaging of cancer cells in vitro. These erythrocyte-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 48 publications
4
69
0
Order By: Relevance
“…Further molecular specificity of NETs can be achieved by functionalizing their surface with appropriate targeting moieties such as antibodies [48]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further molecular specificity of NETs can be achieved by functionalizing their surface with appropriate targeting moieties such as antibodies [48]. …”
Section: Resultsmentioning
confidence: 99%
“…A key advantage of erythrocyte-derived constructs as compared to liposomal particles is that the former can potentially have extended circulation time due to preserved membrane proteins that prevent phagocytosis by immune cells. In a previous study [48], we demonstrated that CD47, a membrane glycoprotein, which impedes phagocytosis [38,39], remains on the surface of NETs. Other investigators have reported that polymeric nano-constructs, coated with erythrocyte-derived membranes, were retained in mice blood for three days with circulation half-life of nearly 40 hours [49].…”
Section: Introductionmentioning
confidence: 99%
“…A schematic representation of the fabrication of tPA‐conjugated NETs is shown in Figure 1 . It depicts the insertion of the lipid linker molecule, 1,2‐distearoyl‐sn‐glycero‐3‐phosphoethanolamine‐polyethylene glycol‐aldehyde group (DSPE‐PEG‐CHO) into the membrane of EGs followed by mechanical extrusion to obtain nanosized EGs . These nanosized EGs were subsequently loaded with NIR imaging agent, ICG, in a hypotonic solution and then conjugated with tPA via amine‐aldehyde chemistry to create a theranostic nanoplatform with imaging and therapeutic capabilities.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from liposomes, [4] synthetic polymers, [5] and magnetic nanoparticles, [8] attention has also been given to the use of biological materials such as erythrocytes as carriers for the delivery of therapeutic payloads to target sites. [9][10][11][12] One feature of normal erythrocytes is their naturally long circulation time (≈90-120 d), attributed to the presence of "self-marker" proteins on their surface. [13] Owing to this feature, constructs derived from erythrocytes may offer a promising approach for increased circulation time of their payload within the vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their cancer drug delivery roots, nanoerythrosomes can be used for the delivery of photoactivatable agents for imaging and photothermal therapy [142], antihypertensive drugs [143], and perfluorocarbons for acoustic responsiveness [144]. Nanoerythrosomes have also been bestowed additional targeting functionality via the conjugation of antibodies to a polymeric tether [145]. Beyond RBCs, stem cells are a popular source of membrane material due to their tumor targeting ability.…”
Section: Cell Membrane-based Nanostructuresmentioning
confidence: 99%